An Experimental Study on Clustering Technique Employed by The Extrovert and Introvert Learners in Reading Comprehension at Fishery Faculty of PGRI University Palembang - Santi Mayasari (Universitas PGRI Palembang, 2016)
ABSTRACTThis study was conducted to investigate An Experimental Study on Clustering Technique Employed by The Extrovert and Introvert Learners in Reading Comprehension at Fishery Faculty of PGRI University Palembang. This study applied experimental method with factorial design. There were 40 students as the population. From 40 students, 30 students were taken as the samples of this research by using two stage random sampling. The statistical analyses used were Independence t-test and Two-way ANOVA. The distribution of both experimental and control group score were normal, since the significant value was higher than 0.05. The data of Clustering Technique and Conventional Technique were homogeneous since the result of homogeneity of variance testing indicated that the significant value of all the data was higher than the significant of p-output (0.05).Furthermore, it was found that (1) there is any significant difference in reading comprehension achievement between extrovert and Introvert students who are taught byusingclustering technique. (2) there is any significant difference in readingcomprehension achievement betweenextrovert and introvertstudents who are taught by using conventional technique. (3) there is any significant difference in reading comprehensionachievementbetween extrovert and introvertstudents who are taught byclustering technique andthosewho are taught byusing conventional technique. (4) there was no any significant interaction effectof clustering technique and extrovert and introvert students onreadingcomprehension achievement. the alternative hypothesis (Ha) was rejected and null hypothesis (Ho) was accepted. Key Word: Clustering Technique, Extrovert and Introvert, ReadingComprehension